Drive-By Solidarity: Conceptualizing the Temporal Relationship between #BlackLivesMatter and Anonymous's #OpKKK. Issue 2 (1st December 2022) - Wright, Jared M.; Kelly-Thompson, Kaitlin; Weldon, S. Laurel; Goldwasser, Dan; Einwohner, Rachel L.; Sinclair-Chapman, Valeria; Tormos-Aponte, Fernando
Abstract: This article offers a theoretical and empirical exploration of a form of solidarity in which one group spontaneously mobilizes in support of another, unrelated group. It is a fleeting solidarity based not on shared identity but on temporarily aligned goals, one aimed less at persistence and more at short-term impact. We call this drive-by solidarity because of its spontaneous, unilateral, and unsolicited nature. We argue that it is a "thinner" form of solidarity in comparison to "thicker" forms usually conceptualized in the social movement literature. We examine the case of Anonymous's "Operation KKK" (#OpKKK), an online hacktivist campaign to expose Ku Klux Klan members carried out in support of #BlackLivesMatter protesters in Ferguson, Missouri, in November 2014, and we use social media data to show that, while BLM and Anonymous networks temporarily coordinated during the protests, there is no subsequent evidence of long-term coordination.